(untitled) (Journal of Information Technologies in Education (ITE), 2016)
Efficiency of Chi-square criterion and Fisher’s angular transformation for statistical hypothesis testing are investigated at small samples with computer-based model. The results show that both criteria give satisfactory accuracy even at small samples. Accuracy zones of determination of the false positive rate (type I error) are analysed on the base of stochastic computational experiments. Comparison of sensitivities of investigated tests is shown as a function of samples size for some cases.